Say no to the duke [large type] - James, Eloisa (James, Eloisa. Wildes of Lindow Castle., 2019)
"Lady Betsy Wilde's first season was triumphant by any measure, and a duke has proposed--but before marriage, she longs for one last adventure. No gentleman would agree to her scandalous plan--but Lord Jeremy Roden is no gentleman. He offers a wager. If she wins a billiards game, he'll provide the breeches. If he wins...she is his, for one wild night. But what happens when Jeremy realizes that one night will never be enough? In the most important battle of his life, he'll have to convince Betsy to say no to the duke" --